An Evaluation of the Acromion Process of Left Scapula (Green Life Medical College Journal, 2025)
Introduction: Acromion process projects forward almost at right angles from the lateral end of the spine and over-hangs the glenoid cavity. The medial acromial border is short, bearing anteriorly a small, oval facet for articulation with the clavicle’s lateral end. Morphological types of acromion process are helpful for orthopaedic surgeons in surgical repair of shoulder joint. The anatomical and morphological variations of the acromion and related structures of shoulder joint have clinical importance. This study was carried out to observe the morphological variation of acromion process. Methods: This cross-sectional study was conducted in the department of Anatomy, Dhaka Medical College, Dhaka, during the period of July 2017 to June 2018. Shoulder radiograph of lateral view and oblique view were taken from 100 adult male & female attending the Radiology & Imaging Department of Dhaka Medical College & Hospital, Dhaka, aged between 25 to 50 years. From these images morphological measurements, length of acromion process, breadth of acromion process, acromio-coracoid distance, acromio-glenoidal distance were measured. Results: The length & breadth of the acromion process, the acromio-coracoid distance & the acromioglenoidal distance were significantly higher in male than female. Conclusion: The present study reveals significant difference in morphological measurements of acromion process. The various dimensions of adult acromion process will serve as a reference and will assist the surgeon to be used in the operative technique.Green Life Med. Col. J. 2025; 10(1): 8-12